Identification and analysis of short-term and long-term salt-associated lncRNAs in the leaf of Avicennia marina - Lingling Wang; Yixuan Fu; Zixin Yuan; Jingyi Wang; Yali Guan (BMC Plant Biology, 2024)
Abstract As a highly salt-resistant mangrove, Avicennia marina can thrive in the hypersaline water. The leaves of Avicennia marina play a crucial role in salinity stress adaptability by secreting salt. Although the functions of long non-coding RNAs (lncRNAs) in leaves remain unknown, they have emerged as regulators in leaf development, aging and salt response. In this study, we employed transcriptomic data of both short-term and long-term salt treated leaves to identify salt-associated lncRNAs of leaf tissue. As a result, 687 short-term and 797 long-term salt-associated lncRNAs were identified. Notably, both short-term and long-term salt-associated lncRNAs exhibited slightly longer lengths and larger exons, but smaller introns compared with salt-non-associated lncRNAs. Furthermore, salt-associated lncRNAs also displayed higher tissue-specificity than salt-non-associated lncRNAs. Most of the salt-associated lncRNAs were common to short- and long-term salt treatments. And about one fifth of the downregulated salt-associated lncRNAs identified both in two terms were leaf tissue-specific lncRNAs. Besides, these leaf-specific lncRNAs were found to be involved in the oxidation–reduction and photosynthesis processes, as well as several metabolic processes, suggesting the noticeable functions of salt-associated lncRNAs in regulating salt responses of Avicennia marina leaves.